Sensitivity of two Australian melanoma risk tools to identify high‐risk individuals among people presenting with their first primary melanoma. (6th May 2022) - Tan, Katrina; Lo, Serigne N.; Cust, Anne E.; Wolfe, Rory; Mar, Victoria
Abstract: Aims: Regular skin examinations for early detection of melanoma are recommended for high‐risk individuals, but there is minimal consensus regarding what constitutes 'high‐risk'. Melanoma risk prediction models may guide this. We compared two online melanoma risk prediction tools: Victorian Melanoma Service (VMS) and Melanoma Institute Australia (MIA) risk tools; to assess classification differences of patients at high‐risk of a first primary melanoma. Methods: Risk factor data for 357 patients presenting with their first primary melanoma were entered into both risk tools. Predicted risks were recorded: 5‐year absolute risk (VMS tool and MIA tool); 10‐year, lifetime, and relative risk estimates (MIA tool). Sensitivities for each tool were calculated using the same high‐risk thresholds. The MIA risk tool showed greater sensitivity on comparison of 5‐year absolute risks (90% MIA vs 78% VMS). Patients had significantly higher odds of being classified as high or very‐high risk using the MIA risk tool overall, and for each patient subgroup. Using either tool, patients of male gender or with synchronous multiple first primary melanomas were more likely to be correctly classified as high‐ or very‐high risk using 5‐year absolute risk thresholds; but tumour invasiveness was unrelated to risk. Classification differed when using the MIA risk categories based on relative risk. Conclusions: Both melanoma risk prediction tools had high sensitivity for identifying individuals at high‐risk and could be used for optimising prevention campaigns. The choice of which risk tool, measure, and threshold for risk stratification depends on the intended purpose of risk prediction, and ideally requires information on specificity.